Expert Humans : critical leadership skills for a disrupted world - Jenkins, Michael, 1961- (Emerald Publishing Limited, 2021)
'Expert Humans: Critical Leadership Skills for a Disrupted World 'examines the critical leadership concepts of Altruism, Compassion and Empathy (ACE) and their application to the great disruptors of today: sustainability, global health, inequality, digital transformation and erosion of trust - from social, historical and psychological perspectives - to support the development of more human workplaces and a better world. The book investigates these ACE behaviours and attributes in depth to show how they can strengthen existing leadership capability. With more ACE leaders in the field the challenges of our disrupted world can be better addressed, and by so doing, create more human workplaces and a more humane society for now and for the future. Drawing on data from the social sciences, close human observation, stories of working people and mini-case studies from around the world - 'Expert Humans' encourages the reader to adopt a more human - and effective - way of living, working and being. This book is intended as a gentle provocation to leaders of small, medium and large organisations, as well as to human resources and organisational development professionals - to help change the nature of what it takes to be a leader, for good.
Includes index.
Keywords: Leadership -- Psychological aspects.; Altruism.; Compassion.; Empathy.; Work environment.; Business & Economics -- Human Resources & Personnel Management.; Organizational theory & behaviour.; elektronické knihy; electronic books